Ben Cao Gang Mu. - Li, Shizhen (Ben Cao Gang Mu: 16th Century Chinese Encyclopedia of Materia Medica and Natural History Series., 2024)
Volume I is divided into two parts. Part A of volume 1 in the Ben cao gang mu series offers a translation of chapters 1 and 2 and portions of chapter 3. Chapters 1 and 2 are devoted to introducing the history of materia medica. Chapter 3 is devoted to pharmaceutical drugs for diseases. Chapter 3 is continued, along with chapter 4, in part B of volume I. The Ben cao gang mu is a sixteenth-century Chinese encyclopedia of.